Synthesis, characterization, and application of silver nanoparticle‐thiophenol nanocomposite film on the glassy carbon surface. (7th October 2013) - Güzel, Remziye; Ekşi, Haslet; Üstündağ, Zafer; Solak, Ali Osman
Abstract : In this study, 4‐thiophenol modified glassy carbon electrode was prepared by the reduction of 4‐diazothiophenol tetrafluoroborate salt. Silver nanoparticles were attached to the thiophenol modified surface to prepare a thiophenol‐silver nanoparticle composite film. 4‐Aminothiopenol molecules were deposited by self‐assembling technique to form multi‐layered nanofilms of TP/SNP/PhNH2 on glassy carbon substrate. These surfaces were characterized by cyclic voltammetry, electrochemical impedance spectroscopy, X‐ray photoelectron spectroscopy, reflectance‐absorption infrared spectroscopy, and ellipsometry at each multilayer film growth process. Atomic force microscopic images of GC/TP/SNP/PhNH2 surfaces were also acquired. The characterization methods show that the amine group containing surface permits the subsequent modification by a variety of coupling reactions for the immobilization of more complex systems. An application of the electrode modification for the determination of uric acid with a significantly lower detection limit is described. Copyright © 2013 John Wiley & Sons, Ltd.